2011
DOI: 10.1590/s0103-84782011001100012
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia experimental para avaliação de custos de produção e utilização de biodiesel: estudo de caso de quatro ésteres metílicos e óleo diesel comercial

Abstract: Metodologia experimental para avaliação de custos de produção e utilização de biodiesel: estudo de caso de quatro ésteres metílicos e óleo diesel comercial Experimental methodology for assessing the cost of biodiesel production and use biodiesel: a case study of four methyl esters and commercial diesel fuel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…BUYUKKAYA (2010) working with pure canola oil (B100) compared to commercial diesel B5 observed an increase in power of 8.5% with B5. FIORESE et al (2011) found reduction of 2.0% in these same mixtures. According to the authors, this is due to of the lower caloric power in biodiesel.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…BUYUKKAYA (2010) working with pure canola oil (B100) compared to commercial diesel B5 observed an increase in power of 8.5% with B5. FIORESE et al (2011) found reduction of 2.0% in these same mixtures. According to the authors, this is due to of the lower caloric power in biodiesel.…”
Section: Resultsmentioning
confidence: 62%
“…Nevertheless, it is known that in certain proportions of the two fuels (mineral diesel and biodiesel), there are significant change on engine performance and emission levels. Some studies show that the use of pure biodiesel in vehicle diesel cycle engines reduces the torque and consequently the power generated (MAZIERO et al, 2006;OZSEZEN et al, 2009;BUYUKKAYA, 2010;FIORESE et al, 2011;NIETIEDT et al, 2011) and increases the time consumption and minimum specific consumption (GODESA, et at. 2010;NIETIEDT et al, 2011;REIS et al, 2013;ÖZENER et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Os custos fixos são os valores das operações como mão de obra e manutenções nos equipamentos. Já para os custos variáveis, se tem o valor de todos os insumos necessários para a fabricação do biodiesel (FIORESE et al 2011). Segundo este mesmo autor, o custo da compra pela matéria-prima a ser utilizada na produção de biodiesel pode chegar a 85% do valor total da produção.…”
Section: Resultados E Discussõesunclassified
“…[39] assessed the cost of producing biodiesel from soybean, sunflower, chicken and beef tallow relative to commercial diesel and found that overall the best value (variable costs þ fixed costs) per liter of biodiesel produced was obtained for biodiesel from tallow, followed by chicken, soybean and sunflower, respectively (Table 4). According to the authors, the methodology showed that the costs go beyond the because of production expenses, and procurement, because the consumption of each fuel is distinct, as has happened with gasoline and ethanol.…”
Section: Resultsmentioning
confidence: 99%